ChemInform Abstract: Synthesis, Characterization and Catalytic Activity of New Bis(N‐2, 6‐diphenylphenol‐R‐salicylaldiminato)Pd(II) Complexes in Suzuki—Miyaura and CO2 Fixation Reactions. Issue 34 (4th August 2016) - Oncel, Nurdal; Kasumov, Veli T.; Sahin, Ertan; Ulusoy, Mahmut
Abstract: Novel Pd(II)‐salicylaldimine complexes are synthesized and their ability to catalyze the Suzuki—Miyaura coupling of aryl bromides as well as the formation of cyclic carbonates from epoxides and CO2 is evaluated.